2021
DOI: 10.21203/rs.3.rs-384224/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluorescence of Ocular Surface in a Covid -19 Patient After Favipiravir Treatment: a Case Report

Abstract: BackgroundFavipiravir is used in treatment of Covid-19 patients. We aimed in this case report to share of ocular surface fluorescence in a patient after Favipiravir treatment.Case PresentationA 20 years-old male ,with no medical history, applied to us with blurry vision and blue light reflection after Covid-19 treatment with Favipiravir. We observed bilateral fluorescence on his eyes and fluorescence of his nails. Biomicroscopic examination was insignificant.Conclusion We investigated the fluorescence of favip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…17 The UV light source used in this report had 365-395 nm wavelength, while Wood's lamp has a wavelength between 320 and 400 nm. 20 Therefore, we also examined the favipravir tablet under Wood's lamp and, similar to that of Doran et al, 19 we detected fluorescence in the fragmented and dissolved forms, while fluorescence was not observed in the whole tablet.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…17 The UV light source used in this report had 365-395 nm wavelength, while Wood's lamp has a wavelength between 320 and 400 nm. 20 Therefore, we also examined the favipravir tablet under Wood's lamp and, similar to that of Doran et al, 19 we detected fluorescence in the fragmented and dissolved forms, while fluorescence was not observed in the whole tablet.…”
Section: Discussionsupporting
confidence: 71%
“…Hyperuricemia, QTc prolongation and teratogenity are associated with the use of this agent, and short‐term use is advocated. Doran et al 19 reported ocular surface fluorescence in their patient following favipravir treatment for COVID‐19. The patient had visual impairment which started with the initiation of favipravir therapy and resolved after cessation of it.…”
Section: Discussionmentioning
confidence: 99%